2018
DOI: 10.1093/femsec/fiy072
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of terminal oxidases in two marine bacterial strains exposed to nanomolar oxygen concentrations

Abstract: The final step of aerobic respiration is carried out by a terminal oxidase transporting electrons to oxygen (O2). Prokaryotes harbor diverse terminal oxidases that differ in phylogenetic origin, structure, biochemical function, and affinity for O2. Here we report on the expression of high-affinity (cytochrome cbb3 oxidase), low-affinity (cytochrome aa3 oxidase), and putative low-affinity (cyanide-insensitive oxidase (CIO)) terminal oxidases in the marine bacteria Idiomarina loihiensis L2-TR and Marinobacter da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…S1b ). A continuous expression of low-affinity caa 3 -type TOs at low O 2 concentrations was previously reported in aerobic marine bacterial species ( 19 , 49 ); however, in that study ( 19 ), the high-affinity cbb 3 -type TO was upregulated at <0.2 μmol O 2 liter −1 . In our study, we did not observe any measurable contribution via transcriptomics or qPCR of the high-affinity cbb 3 -type TO in any of the strains at 10 to 0.001 μmol O 2 liter −1 , although we cannot completely rule out the possibility of a minor contribution (undetectable with our current methods) of the cbb 3 -type TO.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…S1b ). A continuous expression of low-affinity caa 3 -type TOs at low O 2 concentrations was previously reported in aerobic marine bacterial species ( 19 , 49 ); however, in that study ( 19 ), the high-affinity cbb 3 -type TO was upregulated at <0.2 μmol O 2 liter −1 . In our study, we did not observe any measurable contribution via transcriptomics or qPCR of the high-affinity cbb 3 -type TO in any of the strains at 10 to 0.001 μmol O 2 liter −1 , although we cannot completely rule out the possibility of a minor contribution (undetectable with our current methods) of the cbb 3 -type TO.…”
Section: Discussionsupporting
confidence: 49%
“…At nanomolar O 2 concentrations, microorganisms transition from aerobic respiration to anaerobic-based metabolism (substrate-level phosphorylation or anaerobic respiration), referred to as the Pasteur point ( 17 , 18 ). To the best of our knowledge, gene expression-based investigations of terminal oxidases at nanomolar O 2 concentrations are scarce (e.g., Gong et al reported expression at O 2 levels of ≤200 nmol [ 19 ]), and therefore, it is mostly speculated that the high-affinity terminal oxidases are primarily responsible for energy production at low-nanomolar O 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome c oxidases, both aa3- and cbb3-type, were widespread in all three lake environments and frequently co-occurred within MAGs. aa3-type cytochromes are associated with high oxygen concentrations, while cbb3-type cytochromes are associated with low oxygen concentrations (Gong et al, 2018). The presence of genes encoding both types suggests the flexibility to operate under a range of oxygen concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Biogeochemical characteristics, including temperature, nutrients, salinity, and DO, are the important regulators of bacterial community composition in many marine ecosystems (Biddanda et al, 2001;Naqvi, 2006;Paulmier and Ruiz-Pino, 2009;Guo et al, 2018;Gao et al, 2020). The temperature of surface water in the Indian Ocean is closely related to the seasonal variation of the monsoon.…”
Section: Correlation Between Bacterial Taxa and Environmental Parametersmentioning
confidence: 99%